Theoretical modelling of the chemical reactivity of fresh biomass chars under non-catalytic conditions. (February 2019) - Wang, Xiaohan; Song, Qianshi; Wang, Ning; Su, Hang; Zeng, Xiaojun; Yang, Weibin
Highlights: A comprehensive model was developed to describe the biomass char reactivity. The model is based on the simple gas-solid collision theory and fractal theory. The effects of thermal annealing and the pore breaking phenomenon were considered. Good agreement is obtained between the model results and the experimental data. Abstract: This study developed a model for the chemical reactivity of fresh biomass chars, and built a calculation equation for the char gasification rate using simple gas-solid collision theory (SCT). The effects of pore breaks, pore collapse and thermal annealing on the char reactivity were considered in the modelling. Experimental tests for six acid-washed biomass chars were performed under a CO2 atmosphere and used a thermo-gravimetric analyzer (TGA) over the temperature range of 1073–1273 K. The results showed that the reactivity of fresh char could be predicted quantitatively by some characteristic properties of certain kind of biomass and their combined parameters. For the instability of the biomass char structure, the internal pore length and gasification temperature showed a good exponential relationship. Good agreement was achieved, and the applicability of the model was demonstrated by comparing the predicted results with experimental data.